Mother’s Perceptions About Healing Of Perineal Wounds In Post Partum At Khairani Clinic Medan Marelan District - Helena Fransysca; Nurdiana Manurung (Sean Institute, 2023)
Correct treatment of perineal wounds caused by rupture or episiotomy due to birth trauma can prevent infection and speed up the healing process. Apart from wound care, nutrition and movement are also very supportive in speeding up the healing process of perineal wounds in post partum mothers. The research aims to obtain post-partum mothers' perceptions regarding perineal wound healing in terms of maternal nutrition, wound cleanliness (hygiene) and movement as soon as possible (early mobilization). This type of research is cross sectional, the sample method is total sampling with a population of all mothers who gave birth normally at the Khairani Clinic, namely 33 people, the research was conducted in May 2023. The results of research on mothers' perceptions of nutrition regarding the healing of perineal wounds during post partum were not good, amounting to 16 people (48.5%), the mother's perception about wound cleanliness (hygiene) is not good, namely 16 people (38.5%), the mother's perception about moving as soon as possible (early mobilization) is not good, namely 12 people (36.4%) . Post Partum mothers' overall perception of perineal wound healing was 12 people (36.4%), 14 people had a good perception (42.4%) and 7 people (21.2%) had a poor perception. Post Partum mothers' overall perception of perineal wound healing was 12 people (36.4%), 14 people had a good perception (42.4%) and 7 people (21.2%) had a poor perception. It is hoped that post partum mothers will increase their perception about perineal wound healing during post partum, especially regarding nutrition, cleanliness and perineal wound care (Hygiene) and movement as soon as possible (early mobilization) so as to speed up the healing process of perineal wounds.